2006
DOI: 10.1111/j.1439-0450.2006.00922.x
|View full text |Cite
|
Sign up to set email alerts
|

Sero‐epidemiology of Canine Leptospirosis in Trinidad: Serovars, Implications for Vaccination and Public Health

Abstract: A sero-epidemiological study on canine leptospirosis was conducted in house, stray, farm and hunting dogs, as well as in suspect cases of clinical canine leptospirosis. Serum samples were collected from apparently healthy (vaccinated and nonvaccinated), house dogs. A questionnaire was administered to the owners to elicit information on risk factors for leptospirosis. The microscopic agglutination test was used to screen for leptospirosis using 17 international serovars. Reciprocal titres of between 100 and <80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 33 publications
4
29
0
Order By: Relevance
“…In the acute clinical form of canine leptospirosis, members of Icterohaemorrhagiae are most commonly reported as serovar Copenhageni in Trinidad [1] and Australia [7] or Icterohaemorrhagiae in Japan [8] and Brazil [9].…”
mentioning
confidence: 99%
“…In the acute clinical form of canine leptospirosis, members of Icterohaemorrhagiae are most commonly reported as serovar Copenhageni in Trinidad [1] and Australia [7] or Icterohaemorrhagiae in Japan [8] and Brazil [9].…”
mentioning
confidence: 99%
“…In the majority of studies, it has been shown that farmers are usually involved in disease in comparison with other professions. In the study of Perret et al (2005) in Chile, the incidence rate of the disease among the farmers was reported 72% [16]. Slack et al (2010) had mentioned that the most important risk factors of this disease were occupational factors, direct or indirect contact with the animals or their dead bodies, with grass and bushes, swimming, hunting, aquatic sports, and traveling to hot and rainy areas, suggesting the important influence of the type of occupation on the disease outbreak [1,17].…”
Section: Discussionmentioning
confidence: 96%
“…According to Adesiyuncriteria [11], for determining leptospirosis infection, 5 dogs with dilution titers between 1:800 and 1:3200 at the moment of the study coursed with acute leptospirosis, and leptospipuria could contaminate their surroundings, facilitating the disease's transmission to other mammals, such as rats, dogs and even humans. The same authors mention that low titers of 1:100 and 1:200 are considered to be indicative of immunological anamnesis due to a previous infection of the animal.…”
Section: Discussionmentioning
confidence: 99%
“…The animal's reproductive age and the Leptospira seropositivity are possibly related to sniffing habits and the licking of external genitalia by infected males and females in heat [14] [21]. However, older dogs are more likely to have been exposed to leptospirosis at some point and, therefore, are likely to present antibodies for different serotypes due to immunological anamnesis [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation